The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1007/s40011-015-0616-8
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Evaluation of Seaweed on Nutrient Digestibility, Nitrogen Balance, Milk Production and Composition in Sahiwal Cows

Abstract: Twelve lactating Sahiwal cows were divided into three equal groups on the basis of milk yield (mean 8.39 L/day), parity and body weight. All the animals were fed concentrate mixture along with wheat straw and green oats (Concentrate mixture and roughages as 50:50; green oat and wheat straw as 60:40) as total mixed ration for 126 days. While group T1 was fed ration consisting of concentrate mixture without any additional mineral mixture and common salt, group T2 had 2 % mineral mixture and 1 % salt in their con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 18 publications
(20 reference statements)
0
15
1
Order By: Relevance
“…In contrast our results, some studies found no effect by adding seaweeds on any digestion coefficient i.e. Singh et al (2017) found no effect of macroalgae (Sargassum wightii) on digestion coefficient of Sahiwal cows. Also, Zhou et al (2018) found that brown seaweed had no effect on the digestibility coefficients of various nutrients in ram.…”
Section: Digestibility Trialcontrasting
confidence: 99%
See 2 more Smart Citations
“…In contrast our results, some studies found no effect by adding seaweeds on any digestion coefficient i.e. Singh et al (2017) found no effect of macroalgae (Sargassum wightii) on digestion coefficient of Sahiwal cows. Also, Zhou et al (2018) found that brown seaweed had no effect on the digestibility coefficients of various nutrients in ram.…”
Section: Digestibility Trialcontrasting
confidence: 99%
“…They are also rich source of other minerals like sodium, potassium, magnesium, chlorine, sulfur, phosphorus, iodine, iron, zinc, copper, selenium and molybdenum (Archer et al, 2008;Holdt and Kraan, 2011;Rey-Crespo et al, 2014;Ventura and Castañón, 1998). High mineral content makes it a potential additive to animal feedstuffs for replacing a part or whole of the mineral supplementation (Singh et al, 2017). Macroalgae have anti-bacterial, anti-viral, antioxidant, and anti-inflammatory properties that enhance animal health and function (Bach et al, 2008) because, they contain many biologically active compounds such as fucoidan, betaine, and glucans (Archer et al, 2008;Holdt and Kraan, 2011), which enhance animal's immunity and carcass quality (Singh et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given that main drivers for productivity, production efficiency and milk composition are animal breed, intakes, and types of forages and concentrates [ 53 , 54 ], it is likely that the relatively small amount of seaweed supplementation to dairy cow diets (0 to 158 g/cow/day) in the present study was not adequate to cause any impact on these parameters. In contrast, Singh et al [ 55 ] reported that S. wightii supplementation at 20% to concentrate DM showed increased milk production in dairy cows. This discrepancy could be attributed to the much larger degree of supplementation as they administered approximately 955 g of seaweed per cow per day and indicated that there might be unidentified bioactive substances within the seaweed that may have positively affected milk yield at such high supplementation rates.…”
Section: Discussionmentioning
confidence: 94%
“…Addition of sea seaweeds showed inhibitory effect on rumen fermentation resulting in decreased total gas Table 3 Effect of supplementation of graded levels of sea weed product on digestibility, microbial biomass and energy value under in vitro conditions TDMD: true dry matter digestibility, TOMD: true organic matter digestibility, ME: metabolisable energy, MBP: microbial biomass production production, methane production and volatile fatty acids production under in vitro conditions (Machado et al 2014). There were no significant changes in digestibility of nutrients in Sahiwal cows when mineral mixture (3%) in the concentrate was replaced by 20% Sargassum wightii (Singh et al 2015).…”
Section: Supplementary Effects Of Swp On Rumen Fermentation Variablesmentioning
confidence: 89%